Gastrodin Alleviates Oxidative Stress-Induced Apoptosis and Cellular Dysfunction in Human Umbilical Vein Endothelial Cells via the Nuclear Factor-Erythroid 2-Related Factor 2/Heme Oxygenase-1 Pathway and Accelerates Wound Healing In Vivo - Lin, Jialiang; Shi, Yifeng; Miao, Jiansen; Wu, Yuhao; Lin, Hao; Wu, Jianwei; Zeng, Weimin; Qi, Fangzhou; Liu, Chen; Wang, Xiangyang; Jin, Haiming (Frontiers in Pharmacology, 2019)
Angiogenesis, primarily carried out by endothelial cells, is an important biological process in wound healing. Excessive levels of reactive oxygen species (ROS) produced at wound sites cause endothelial cell dysfunction, leading to delayed wound healing. Gastrodin (GAS), the major active component of Gastrodia elata, has been previously reported to possess antioxidative effects. In our study, the protective effect of GAS on human umbilical vein endothelial cells (HUVECs) under oxidative stress and its function in wound healing were investigated. The results show that treating HUVECs with GAS attenuated tert-butyl hydroperoxide (TBHP)-induced apoptosis and cellular dysfunction, including cellular tube formation, migration, and adhesion. Mechanistically, we found that GAS protects HUVECs from TBHP-induced cellular apoptosis by activating the nuclear factor (erythroid-derived 2)-like 2 (Nrf2)/haem oxygenase 1 (HO-1) pathway. An in vivo study illustrated that the oral administration of GAS enhances vascularization in regenerated tissue and facilitates wound healing. The findings of this study demonstrated that GAS may serve as a potential agent that accelerates wound healing.